APPLICATIONS DATABASE XYZ ON CAMPUS LIBRARY USING MICROSOFT VISUAL BASIC 6.0 AND MICROSOFT ACCESS 2007 - Suminah Suminah; Susi Widayati, SKom., MM Susi Widayati, SKom., MM (Jurnal Sistem Informasi, 2010)
It describes the application of scientific writing Visual Basic language into the work activities of the ministry, which is very influential on all their activities which include searching for data processing member data, book data search, data inspection of books borrowed from the library. This application is made data processing member, the data book on Campus XYZ. Processing of this data can be stored so it can be used as checking if there are any errors.In order to produce a better view, then this program is made by using the programming language Microsoft Visual Basic 6.0. Also in this study also explained about the making of the application programs and their application in the computer.